Associations of sedentary behavior and physical activity with physical measurements and dyslipidemia in school-age children: a cross-sectional study - Wei Zheng; Yun Chen; Ai Zhao; Yong Xue; Yingdong Zheng; Zhishen Mu; Peiyu Wang; Yumei Zhang (BMC, 2016)
Abstract Background Physical activity and sedentary behavior are common factors influencing cardiovascular health. However, how school and leisure-time activity/sedentary behavior are associated with physical fitness and blood lipid levels in primary school children in consideration of gender disparity remains unclear. Methods Data was obtained from a health and nutrition survey on primary school children from nine areas in China. The association between physical activities/sedentary behaviors (school and leisure-time physical activity levels, screen time, and other sedentary behaviors) and anthropometric measurements/prevalence of dyslipidemia were examined by multilevel analysis (the individual level, class level, grade level, and investigation area level) adjusted for age, energy intake and family income. Results A total of 770 participants (average age = 9.4 ± 1.7 years) were included. Prevalence of dyslipidemia was 10.9%. Prevalence of dyslipidemia was associated with screen time in boys [OR = 3.04, 95% CI (1.24-7.45)] and inversely associated with leisure-time physical activity in boys [OR = 2.22, 95% CI (1.08-4.56)] and school-time activity in girls [OR = 5.34, 95% CI (1.18-24.16)]. Conclusions Physical activity-but not sedentary behavior-was significantly associated with dyslipidemia in both genders. Increasing leisure-time physical activity for boys and school-time physical activity for girls may be critical.